Uniplanar External Fixator as a Definitive Treatment for Open Fracture of Tibia - Muhammad Inam, Wajid Rehan, Osama Bin Zia, Aman Ullah Khan Kakar, Syed Abdur Rub Abidi, Abdul Rehman Khan, Muhammad Talha Khalil, Tauseef Raza, Abdulakbar, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: Tibia is exposed to majority of trauma and accidents due to its location in the body. That’s why most of time it sustains open fracture in trauma and have high frequency of infected non union due to precarious blood supply. Definitive treatment with ex fix is a very good idea for poor people as one can save money and avoid multiple surgeries as the patient cannot afford it Objective: To evaluate the results of Definitive treatment with uniplanar external fixator in open fracture management of tibia in terms of healing. Material and Method: This Case Series study was conducted from January 2017 to December 2022 in Akbar Medical Center Dabgari Garden Peshawar Pakistan. A total number of 97 patients of either gender having age range of 15 to 60 years with open fracture of tibia were included. All patients were admitted from outpatient department of the center. All the data collected was entered and analyzed with help of SPSS version 23. The results were evaluated using Association for the Study and Application of the Methods of Ilizarov (ASAMI) scoring system. Results: There was total 97 patients having age range of 44(15-59) with mean age 31.23.(Std Deviation 11.58). Male patients were 74(76.3%) while female were 23( 23.7%). Delayed union was noted in 11(11.3%), External Rotation in 3(3.1%) Healed without complication in 72(74.2%), Infection in 4(4.1%), one pin broken in 4 (4.1%) and Shortening of less than 1.5 cm was noted 3(3.1%) cases. In 4(4.1%) cases debridement was done as secondary procedure, in one case NA fixator was applied 1(1%) while in 7(7.2%) case bone grafting was done as secondary procedure. Practical Implication: Definitive treatment with ex fix is a very good idea for poor people as one can save money and avoid multiple surgeries as the patient cannot afford it. Conclusion: External fixator is used as a definitive treatment method for open fractures of the tibial shaft caused by high energy trauma either in war times or in motor vehicle accidents has good bone and functional results. Keywords: Tibia, Fracture, Fixator, Uniplanar, Ilizarov